Aspects of Land Administration in the Context of Good Governance - G Pienaar (Potchefstroom Electronic Law Journal, 2009)
Recent international developments have emphasised the importance of good governance in land administration. Good governance practices are inter alia predictable, open and enlightened policy-making; accountable and transparent processes; a professional ethos that combats corruption, bias, nepotism and personal gain; and strict financial control and management of funding. This paper explores aspects of land administration where public funding and interests necessitate the application of good governance practices. The South African land reform programme is divided in three sub-programmes, namely land restitution, land redistribution and tenure reform. Land reform is a vast subject, based on policy, legislation and case law. Therefore it is impossible to deal with good governance principles over the wide spectrum of land reform. Special attention is however given to the land restitution programme in terms of the Restitution of Land Rights Act 22 of 1994 and tenure reform in the rural areas by means of the Communal Land Rights Act 11 of 2004. The purpose is not to formulate a blueprint for good governance or to indicate which good governance principles will solve all or most of the land tenure problems. It is rather an effort to indicate that policies and procedures to improve good governance in some aspects of land reform are urgently needed and should be explored further. The three land tenure programmes have been introduced with some degree of success. Legislation promulgated in terms of these programmes, especially the Restitution of Land Rights Act and the Communal Land Rights Act, is extensive and far-reaching. However, many legislative measures are either impractical due to financial constraints and lack of capacity of the Department of Land Affairs, or are not based on sufficient participation by local communities. Land administration should furthermore be planned and executed in the context of global good governance practices. This includes equal protection; clear land policy principles; land tenure principles according to the needs of individuals and population groups; flexible land registration principles to accommodate both individual and communal land tenure; and appropriate institutional arrangements. It is clear that established good governance principles may solve many of the problems encountered in land administration in South Africa. It is a topic that needs to be explored further.